Comprehensive pharmacy review for NAPLEX - Shargel, Leon, 1941- (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
"This eighth edition of Comprehensive Pharmacy Review reflects the continuing evolution of pharmacy practice and educational requirements. The main objective of the book is to provide a comprehensive study guide for pharmacy students and other candidates who are preparing for the North American Pharmacist Licensure Examination (NAPLEX). This volume represents the contributions of more than 50 specialists who provide wide expertise in pharmaceutical science, pharmacy practice, and clinical pharmacy. Their contributions to Comprehensive Pharmacy Review assure that this review guide is accurate and current as well as written in a comprehensible manner for students, teachers, and practitioners alike. This review publication, along with the separate booklet of simulated NAPLEX exams (Comprehensive Pharmacy Review Practice Exams, 8th edition), provides both guidance and test practice for NAPLEX candidates"--Provided by publisher.